Influence of Social Media on Tourism Business: Current Trends and Future Implications for Bengaluru - George, B; N, Sneha (Atna Journal of Tourism Studies, 2021)
Social media is a powerful marketing tool for the business of tourism. It provides a forum for tourists to make meaningful connections with service providers through social media platforms, and a greater understanding of products and services thereby encouraging active participation and engagement between tourists and service providers. The main objective of this paper is to study the level of exposure received from social media for tourism and the extent of the influence of social media on tourism to understand the implications of social media in the tourism industry, specifically, Bengaluru.